Novel Approaches Towards the Synthesis of Morphinan Derivatives - Gorbachev, Dmitry (2023)
The following work contains two chapters, encompassing two projects. The first chapter describes improvements to the current state-of-the-art process route for the conversion of morphine to a valuable pharmaceutical intermediate noroxymorphone. A mild and industrially applicable Albright-Goldman oxidation was implemented as a key step to improve the process. Utilisation of the Albright-Goldman conditions allowed the combination of the oxidation step with the subsequent diene-forming step, thereby making the overall process more concise and reducing the number of required manipulations. These features are particularly advantageous when applied to the large-scale industrial manufacture. The second chapter describes the successful application of TBADT photocatalysis towards functionalisation of the morphinan scaffold. A series of novel 8-substituted morphinan derivatives were synthesized using a range of coupling partners containing various functional groups. This work demonstrated the utility and applicability of TBADT catalysis towards late-stage functionalisation of natural products under mild conditions.